Amplification of mouse mammary tumor virus genomes in non-mammary tumor cells. - Racevskis, J (1989)
Extra proviral copies of mouse mammary tumor virus (MMTV) are known to be present in the genomes of certain T-cell lymphomas of mice. Analysis of additional non-mammary tumor cell types known to express MMTV transcripts and antigens revealed the presence of extra acquired MMTV proviruses in a pituitary tumor cell line, a macrophage line, and Leydig testicular tumor cells. The nature of the amplified MMTV proviruses in these various tumor cell types differed with regard to copy number and presence of alterations in the long terminal repeat region.